Curricularization of university extension: a bibliometric analysis - Novais Cabral de Oliveira, Carla Viviane; Ribeiro Tosta, Marielce de Cássia; Randow de Freitas, Rodrigo (Brazilian Journal of Production Engineering, 2020)
Extension activities in Brazilian universities have existed since 1911 based on the provision of services. Since then, there has been a commitment on the part of teachers, students and organized civil society to have a solid social commitment between the university and society. For this purpose, Law no. 5,540 / 68; the Forum of Pro-Rectors; the Federal Constitution (1988) and the National Extension Policy (2012). Despite these attempts, extension does not yet have the same importance in the triad (teaching, research and extension) in academic training in undergraduate courses. Thus, in order to minimize this problem, the National Education Plan (PNE) 2014-2024, established that they should be credited in the curriculum of the courses"[...] at least 10% (ten percent) of the total curricular credits required for graduation in university extension programs and projects". Thus, the objective of this article was to carry out a bibliometric analysis on the fulfillment of this strategy. The analysis was performed based on bibliographic research and secondary data through consultation with the CAPES thesis and dissertation database; extension magazines and works published in annals of events. According to bibliometric analysis, it can be concluded that there is little contribution related to the theme and that accreditation brings with it a series of conceptual reflections on extension, as well as the fact that it is a challenge for Higher Education institutions. Findings indicate that each institution must choose the best work strategy according to the level of knowledge and involvement of the academic community.
Keywords: University Extension; Accreditation Curriculum; Graduation; Public Management